2003
DOI: 10.1002/ardp.200300725
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial and Antifungal Isosters of Salicylamides

Abstract: A set of 40 derivatives of 3-hydroxypicolinic acid and 2-sulfanylbenzoic acid, isosteric to salicylanilides was synthesized. The compounds were evaluated for in vitro activity against Mycobacterium tuberculosis, Mycobacterium kansasii and Mycobacterium avium, Candida albicans, Candida tropicalis, Candida krusei, Candida glabrata, Trichosporon beigelii, Aspergillus fumigatus, Absidia corymbifera, Trichophyton mentagrophytes and Microsporum gypseum. Structure-activity relationships of antimycobacterial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 5 publications
(7 reference statements)
0
31
0
Order By: Relevance
“…The methods of the experiments are described in our previous paper [12]. The minimum inhibitory concentrations (MIC) were determined after incubation at 378C for 14 and 21 days.…”
Section: Antimycobacterial Susceptibility Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of the experiments are described in our previous paper [12]. The minimum inhibitory concentrations (MIC) were determined after incubation at 378C for 14 and 21 days.…”
Section: Antimycobacterial Susceptibility Testingmentioning
confidence: 99%
“…Our research was strongly oriented to collaborate with German institutes like Technical University Dresden, Friedrich Schiller University Jena, Hans Knöll Institute Jena, and Maxmilian University in Munich. Approximately ten years ago, we studied antimycobacterial derivatives with the new pharmacophore together with Hans-Dietrich Stachel [10,11] and for several years now, we are investigating the antimycobacterial arylbenzoxazine-2,4(3H)-diones [12].…”
Section: Introductionmentioning
confidence: 99%
“…N-Phenyl and N-benzyl salicylamides were investigated for their antimicrobial [1], antifungal [2], and various antiviral properties [3]. These compounds were also used as topical antimycotics and antiplaque [4], molluscicidal [5] and anthelmentic agents [6].…”
Section: Introductionmentioning
confidence: 99%
“…The classical approach for the synthesis of N-substituted 2-hydroxybenzamides is based on the refluxing of substituted salicylic acid with appropriate amine (aniline, benzylamine, phenethylamine) in chlorobenzene in the presence of phosphorus trichloride for several hours [14,15]. Other synthetic approaches were also reported [16] as microwave assisted synthesis, which reduced total reaction time from several hours to minutes with comparable yields [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several works are reported on the antimycobacterial benzylsalicylamides, [21,22] the activity of isoesters of salicylanilides: 2-sulfanylbenzanilides, N-benzylsulfanylbenzamides 3-hydroxypicolinanilides, and Nbenzyl-3-hydroxypicolinamides. [23] Methylene group modifications of the N-(isothiazol-5-yl)phenylacetamide synthesis and its insecticidal activity are reported by Samaritoni et al [24] Vibrational spectroscopic study of acetate group is reported by Ibrahim and Koglin. [25] The assessment of solid state composition of an active salicylanilide compound by FT-Raman spectroscopy is reported by Spiegeleer et al [26] Diclofenac sodium, which consists of a phenylacetate group, a secondary amino group, and a dichlorophenyl ring, is a well known representative of nonsteroidal anti-inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%